2014
DOI: 10.1371/journal.pone.0105416
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3 Promotes RCAN1 Stability and Nuclear Translocation

Abstract: Regulator of calcineurin 1 (RCAN1; also referred as DSCR1 or MCIP1) is located in close proximity to a Down syndrome critical region of human chromosome 21. Although RCAN1 is an endogenous inhibitor of calcineurin signaling that controls lymphocyte activation, apoptosis, heart development, skeletal muscle differentiation, and cardiac function, it is not yet clear whether RCAN1 might be involved in other cellular activities. In this study, we explored the extra-functional roles of RCAN1 by searching for novel R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For Gene Ontology (GO) enrichment analysis, we employed a Wallenius non-central hypergeometric distribution based on GOseq 23 , which can adjust for gene length bias. KEGG 24 is a database resource for inferring high-level functions and utilities of biological systems such as the cell, organism, and ecosystem from molecular-level data, especially large-scale molecular datasets generated by genome sequencing and other high-throughput experimental technologies ( http://www.genome.jp/kegg/ ). The statistical enrichment of target gene candidates in KEGG pathways was tested using the KOBAS 25 program.…”
Section: Methodsmentioning
confidence: 99%
“…For Gene Ontology (GO) enrichment analysis, we employed a Wallenius non-central hypergeometric distribution based on GOseq 23 , which can adjust for gene length bias. KEGG 24 is a database resource for inferring high-level functions and utilities of biological systems such as the cell, organism, and ecosystem from molecular-level data, especially large-scale molecular datasets generated by genome sequencing and other high-throughput experimental technologies ( http://www.genome.jp/kegg/ ). The statistical enrichment of target gene candidates in KEGG pathways was tested using the KOBAS 25 program.…”
Section: Methodsmentioning
confidence: 99%
“…HDAC1, HDAC3, and HDAC10 increase constitutive SV40 LT protein stability by deacetylating the K697 residue. In the present study, HDAC3 and HDAC8 and their deacetylase were essential for BKPyV infection, and HDAC3 interacted with BKPyV LT. HDAC3 regulates non-histone protein stability by deacetylation, such as cyclin A [ 42 ] and the regulator of calcineurin 1 [ 43 ]. According to the present study, HDAC3 knocked down or repressed its deacetylase activity by specific inhibitors that suppressed BKPyV LT protein expression; thus, HDAC3 might regulate LT protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous HDACs, HDAC3 is widely expressed and conserved in a wide range of species ( 22 ). HDAC3 regulates the c-Jun N-terminal kinase pathway ( 23 ), NF-κB activity ( 24 ), mitogen-activated protein kinase activation ( 25 ) and nuclear translocation of regulator of calcineurin 1 ( 26 ). The present study reported several important observations regarding the involvement of HDAC3 in the molecular mechanisms of AS.…”
Section: Discussionmentioning
confidence: 99%